Transformation of family-based entrepreneurial activities in rural areas - Gugushvi, Temur (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2021)
The shift in policy focus from agriculture to rural development enables rural families to diversify their economic activities. Household-based resources, particularly human capital, are essential for capitalizing on newly developed opportunities. Locals with sufficient resources seize possibilities in agriculture and emerging economic sectors such as tourism. A case study (33 in-depth interviews) of Caucasus mountain households in Kazbegi and Mestia municipalities revealed the importance of human capital in attaining other types of resources, such as social and financial capital, and, ultimately, in the process of family-based economic development. Local families are encouraged to engage in and embrace contemporary farming practices in order to determine the most effective sustainable livelihoods. Along with long-established industries, households employ traditional knowledge to enter entrepreneurial tourism activities.
Keywords: agriculture; Caucasus; človeški kapital; economic development; Georgia; gospodarski razvoj; Gruzija; human capital; Kavkaz; kmetijstvo; podeželje; razvoj podeželja; rural areas